A Quasi-Projection Analysis for Elastic Wave Propagation in Fluid-Saturated Porous Media (Journal of Computational Mathematics, 2021)
This paper deals with the superconvergence phenomena for Galerkin approximations of solutions of Biot's dynamic equations describing elastic wave propagation in fluid-saturated porous media. An asymptotic expansion to high order of Galerkin solutions is used to derive these results.